Co-producing territorial development: public-community strategies for water and food in Imbabura, Ecuador - Toro-Mayorga, Lorena (2021)
This article focuses on the alliances established by the State on the territories with a view to becoming the articulating axis of community processes, in a vertical structure under the guise of participatory and inclusive models. From the experiences of water management and short food commercialization circuits models in Imbabura, this work analyzes, how knowledge is negotiated in the processes of territorial governance and public-community alliances? What are the implications of knowledge co-production processes for the territories? From a perspective of political ecology and territorial development studies, this article analyzes how peasant organizations participate in alliances with public authorities. We found that in a context of water injustice, several community movements in the province seek to participate in and benefit from local and regional development projects. However, these community organizations are forced to negotiate their initial demands to be included in these projects. In parallel, the modernizing ideal, of achieving territorial development from technical notions of modernization, efficiency and professionalization, faces resistance and adaptations from the organizations themselves. A more horizontal negotiation depends on the historical roots of knowledge co-production, according to the actors with whom they are linked.